oblicz
a) 4(x-9)= 2(2x+5)
b)5(x-2)+4(3-x)=9(x+1)-7
c) -2(3x-4)= 3(6-x)- (x-2)
d)4(x-2)-3(x-1)<x+11
e)(x-3)(4-2x)<-2(x+4)(x+1)
f)5(x-1)>6(x+2)-x+1


Odpowiedź :

a) 4(x-9)=2(2x+5)
4x - 36= 4x+10
4x - 4x= 10 + 36
0= 46
b)5(x-2)+4(3-x)=9(x+1)-7
5x - 10 + 12 - 4x= 9x + 9 - 7
x + 2= 9x - 7
x - 9x = -7 -2
-8x= -9 /: (-1)
8x=9
c) -2(3x-4)= 3(6-x)- (x-2)
-6 + 8= 18 - 3x -x + 2
2 = 20 - 4x
2 - 20=-4x
-18= -4x
d)4(x-2)-3(x-1)<x+11
4x - 8 -3x + 3 < x +11
x - 5 < x+11
e)(x-3)(4-2x)<-2(x+4)(x+1)
f)5(x-1)>6(x+2)-x+1
5x - 5 > 6x + 12 - x +1
5x - 5> 5x + 13